Two Monumental Publications Marking the 700th Anniversary of Birth of Charles IV in Current Czech Politics of History - Bartlová, Milena (Dějiny – teorie – kritika, 2017)
This contribution compares two voluminous books which were published to mark the 700th anniversary of birth of Holy Roman Emperor Charles IV in 2016. The author analyses their structure, content, methods used, and their relation to current streams in Czech politics. Despite numerous differences, both books share certain focus on self-celebration of power and symbolic values of the ruler and the Church. This is probably largely due to the fact that as a set of available sources, surviving works of art would lend themselves to alternative representations only with difficulty.